Spread of a Gammabaculovirus within Larval Populations of Its Natural Balsam Fir Sawfly (Neodiprion abietis) Host Following Its Aerial Application - Roger Graves; Christopher J. Lucarotti; Dan T. Quiring (Insects, 2012)
Field trials and assessments of the balsam fir sawfly (Neodiprion abietis) nucleopolyhedrovirus (NeabNPV: Baculoviridae, Gammabaculovirus) against its natural host were conducted in July and August 2002 near Corner Brook, Newfoundland and Labrador, Canada, in naturally regenerated, precommercially thinned stands dominated by balsam fir (Abies balsamea). Two experimental blocks, each with its own untreated control, were established. The purpose of the Island Pond block was to examine the spread of NeabNPV from a 313-ha aerial treatment block out into adjacent populations of balsam fir sawflies. The purpose of the Old Man’s Pond block (2,093 ha) was to determine whether NeabNPV could disperse into populations of balsam fir sawflies within a 200-m zone between spray swaths. NeabNPV was applied to treatment blocks by a Cessna 188B AgTruck aircraft equipped with MicronAir AU4000 rotary atomizers at an application rate equivalent to 1 × 109 NeabNPV occlusion bodies/ha in 2.5 L of 20% aqueous molasses. At Island Pond, NeabNPV infection increased with time following the spray, especially for individuals close to the treatment block, and infection rate decreased to a measured distance of 400 m from the treatment block. At Old Man’s Pond, NeabNPV infection rose higher (80% vs. 15%) and sawfly densities declined more (84% vs. 60%) in the area between spray swaths than in the control block.